Algoritma Natural Language Processing Untuk Aplikasi Penerjemah (Indonesia – Jawa) Menggunakan Metode Speech Processing - Ghirrid, Aria Andros; Sari, Ratih Titi Komala; Aldisa, Rima Tamara (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2024)
Javanese is one of the most widely used regional languages in Indonesia. Apart from that, in several countries such as Suriname, the Netherlands and Malaysia, Javanese is used. The aim of this research is to create a translator application, allowing users to convert speech into written text. In creating a Speech to Text translation application, the Natural Language Processing (NLP) algorithm has a major role. NLP algorithms are used to understand the structure of human language, recognize entities, and translate complex speech into readable text. This study discusses the design and development of a Speech to Text translator application using the NLP algorithm. This application uses deep learning models that have been trained to understand user language variations, accents and intonation.